hERG Channel Blocking Ipecac Alkaloids Identified by Combined In Silico – In Vitro Screening - Kratz, Jadel M.; Mair, Christina E.; Oettl, Sarah K.; Saxena, Priyanka; Scheel, Olaf; Schuster, Daniela; Hering, Steffen; Rollinger, Judith M. (Planta Medica, 2016)
Human ether-a-go-go-related gene channel blocking is associated with QT interval prolongation and increased risk of potentially fatal arrhythmias. As natural products keep increasing in popularity, there is an urgent need for studies assessing human ether-a-go-go-related gene channel-related cardiotoxic risks. We selected 49 plant species based on the results of a pharmacophore-based virtual screening campaign, in parallel with a literature data survey concerning highly consumed herbal medicines with reported cardiac liabilities. Lead-like enhanced extracts were prepared, an initial in vitro screening was performed at 100 µg/mL by voltage clamp on Xenopus oocytes, and five human ether-a-go-go-related gene channel blocking extracts were identified. In accordance to the six virtually predicted alkaloids, the root extract of Carapichea ipecacuanha inhibited human ether-a-go-go-related gene channel currents by 32.5 %. A phytochemical workflow resulted in the isolation and identification of five out of the six virtually predicted alkaloids. All isolates blocked human ether-a-go-go-related gene channel currents to different extents. The major ipecac constituents emetine (1) and cephaeline (2) showed IC50 values of 21.4 and 5.3 µM, respectively, measured by whole-cell patch clamp in HEK293 cells. This is the first report on human ether-a-go-go-related gene channel blockers from C. ipecacuanha. Its roots and rhizomes are used to produce different pharmacopeial ipecac preparations that are mainly used as emetics for poisoning treatment. Our findings raise further questions regarding the safety and over-the-counter appropriateness of these herbal products.
Keywords: Carapichea ipecacuanha; Rubiaceae; ipecac syrup; ipecac alkaloids; hERG channel; patch clamp